Positive Thinking Model for Women Who Have Body Dissatisfaction - Rudi Dwi Maryanto (Dinasti International Journal of Education Management And Social Science, 2023)
This study aimed to establish a correlation between positive thinking and body dissatisfaction among women aged 20 to 40 residing in Sampang. With a quantitative approach, the study surveyed 344 individuals through online questionnaires using Google Forms. Nonparametric statistics, specifically Spearman Brown correlation test, was used for data analysis. Results showed a significant negative relationship between positive thinking (independent variable) and body dissatisfaction (dependent variable), with a Spearman Brown Correlation Coefficient of -0.509 at a significance level (p) of 0.000. The findings suggest that positive thinking can have a significant impact on reducing body dissatisfaction in women. In women, a positive outlook corresponds to reduced body dissatisfaction, meaning that as women become more positive in their thinking, their body dissatisfaction tends to decrease. Conversely, a lack of positive thinking in women leads to an increase in body dissatisfaction.